Computational Intelligence and Sustainable Systems Intelligence and Sustainable Computing - Anandakumar, H.; Arulmurugan, R.; Onn, Chow Chee.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book features research related to computational intelligence and energy and thermal aware management of computing resources. The authors publish original and timely research in current areas of power, energy, temperature, and environmental engineering as and advances in computational intelligence that are benefiting the fields. Topics include signal processing architectures, algorithms, and applications; biomedical informatics and computation; artificial intelligence and machine learning; green technologies in information; and more. The book includes contributions from a wide range of researchers, academicians, and industry professionals. The book is made up both of extended papers presented at the International Conference on Intelligent Computing and Sustainable System (ICICSS 2018), September 20-21, 2018, and other accepted papers on R&D and original research work related to the practice and theory of technologies to enable and support Intelligent Computing applications. Presents the most recent challenges and developments in computational intelligence for sustainable systems and their best practices for application; Includes high quality research contributions from a wide range of scholars, researchers, academicians and professionals; Features expanded papers from the International Conference on Intelligent Computing and Sustainable System (ICICSS 2018), September 20-21, 2018.
Chapter 1. Performance Analysis of Deep Neural Network and Stacked Auto encoder for Image Classification -- Chapter 2. Soft Computing based Void Recovery Protocol for Mobile Wireless Sensor Networks -- Chapter 3. Latest Research Trends And Challenges of Computational Intelligence Using Artificial Intelligence And Augmented Reality -- Chapter 4. Efficient Evolutionary Techniques for Wireless Body Area using Cognitive Radio Networks -- Chapter 5. Artificial Intelligence and Machine Learning for Large-Scale Data -- Chapter 6. Impact of Green Practices on Pakistani Manufacturing Firms' Performance: A Path Analysis Using Structural Equation Modelling -- Chapter 7. Cluster Based Health Monitoring Scheme in Wireless Sensor Networks -- Chapter 8. Design and Implementation of Area and Delay Efficient FXLMS Filter for active Noise Cancellation -- Chapter 9. Aspect based Text Summarization using Map Reduce Optimization -- Chapter 10. A Hill Climbing Approach for Residues Mapping in Protein Structures Alignment -- Chapter 11. Hardcopy Text Recognition and Vocalization for Visually Impaired and Illiterates in Bilingual Language -- Chapter 12. Investigation of Non-Natural Information from Remote Sensing Images: A Case Study Approach -- Chapter 13. Minimization of SCA Attacks by CMOS Based Blurring Gates -- Chapter 14. Linux based Elevator Control System -- Chapter 15. SOS Emergency Ad-Hoc Wireless Network -- Chapter 16. Promoting Greenness with IoT based Plant Growth System -- Chapter 17. Study on the Supply Chain Integration: In the Perspective of Pakistan -- Chapter 18. Multilevel Coding For Multiple Input Multiple Output System.
Keywords: Telecommunication; Computational intelligence; Renewable energy sources; Artificial intelligence; Communications Engineering, Networks; Computational Intelligence; Renewable Energy; Artificial Intelligence